Creating an Afro-sensed, Community-engaged School: Views from Parents and School Personnel. Issue 2 (3rd May 2020) - Shokane, Allucia Lulu; Masoga, Mogomme Alpheus; Blitz, Lisa V.
ABSTRACT: Schools are important for the development and socialization of children to learn to function as responsible citizens, but there can be obstacles, including differences in culture, expectations, and lack of communication between adults at school and home. Family engagement with schools has been shown to improve learner outcomes and minimize differences in culture between home and school. School social work is a specialized field of practice that can strive to engage families, prevent problems, and promote education, but school social workers may not share families' culture, and thus may not know how to offer optimal support. To better understand perceptions, focus groups with parents and school personnel were conducted to explore the question: What cultural indigenous practices can be incorporated in school social work to facilitate family engagement? Four themes were identified that together support indigenous knowledge and encourage local cultures and contexts to integrate Afro-sensed approaches toward a transformed school social work practice.